Comprehensive recovery method for zinc, nickel and cobalt-containing purification slag - LONG YONGBIN; LIU ANRONG; LI SHIPING; ZHONG XIANJIE; WANG ZHENJIE; LIU HONGBO; ZHONG BO (2018)
The invention relates to a comprehensive recovery method for zinc, nickel and cobalt-containing purification slag. The method comprises the following steps: washing the zinc, nickel and cobalt-containing purification slag with hot water till the content of sulfate radicals or chlorine ions of a lotion is smaller than 1g/L and then leaching the purification slag with sodium hydroxide; obtaining zinc and cobalt-containing alkaline leaching liquor and leached slag primarily containing nickel; putting the alkaline leaching liquor in a magnetic field and performing diaphragm electrolysis by takinga magnetic material as an anode and a stainless steel plate as a cathode to obtain metal zinc powder in a cathode region and the cathode and anode slurry primarily containing Co2O3 and Co3O4 in an anode region and the anode; washing and drying the anode slurry, reducing the same directly with hydrogen to obtain metal cobalt powder or sulfuric acid leached out, precipitating oxalic acid to obtain cobalt oxalate, then reduc